HUBUNGAN MINTA BACA DENGAN KEMAMPUAN MENGIDENTIFIKASI UNSUR-UNSUR PEMBANGUN TEKS PUISI KELAS VII SMP NEGERI 40 PADANG - Sinta Wahyuni (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2022)
This study aims to describe students' interest in reading, describe the ability to identify the building blocks of students' poetry texts, and to describe the relationship between reading requests and the ability to identify elements of poetry texts for class VII SMP Negeri 40 Padang. In this study, there were 2 classes as the research sample for class VII.1 as many as 29 students and another class as a test class for class VII.2 questionnaires with 27 students. The sampling technique was carried out using the purposive sampling technique. The instruments used in this research are questionnaires and objective tests. The results of this study are three things. First, the reading interest of class VII students of SMP Negeri 40 Padang obtained anaverage score of 74.24 in the range of 66-75% on a scale of 10, with more than adequate qualifications (LdC). Second, the ability to identify the elements of poetry building for seventh grade students of SMP Negeri 40 Padang obtained an average score of 82,34  in the range of values of 75-85% on a scale of 10, with good qualifications (B). Third, there is a significant relationship between reading interest and the ability to identify elements of poetry building for students of VII SMP Negeri 40 Padang. This shows that reading interest affects students in identifying the building blocks of poetry. This can be seen from the test results which prove that tcount > from ttable, namely 5.40 > 1.70.